Relationship Quality in the Context of Cyber Dating Abuse: The Role of Attachment. (June 2020) - Lancaster, Morgan; Seibert, Gregory S.; Cooper, Ashley N.; May, Ross W.; Fincham, Frank
Cyber dating abuse can lead to negative outcomes for the message receiver and for the relationship. Extending previous research examining problematic technology-based behavior and attachment security, this study examined whether insecure attachment moderates the relationship between cyber dating abuse and relationship quality in emerging adults (N = 177). Through survey methodology, findings detail an interaction between cyber dating abuse and attachment avoidance pertaining to positive, but not negative, relationship quality. Victims of cyber dating abuse who were high in attachment avoidance reported significantly lower positive relationship quality compared to those who are not victims of cyber dating abuse. The present study contributes to a limited body of cyber abuse research within intimate relationships providing a nuanced understanding of the differentiation between positive and negative elements of relationship quality. Implications suggest clinicians should incorporate psychoeducation about the impact of cyber dating abuse to help couples interrupt and improve negative communication through technology.